KONTRIBUSI ATRIBUT PRODUK, KELOMPOK EFERENSI, DAN PROMOSI TERHADAP INFLUENCE POWER ANAK KEPADA ORANG TUA - Jessica Weynata (Jurnal Manajemen dan Pemasaran Jasa, 2014)
The background of this research was due to the fact that children are unique and potential consumers. The objective of this research was to analyze the effect of factors that form the intention to consume among children and how these factors shape the children’s ability to persuade their parents to purchase goods on their behalves.The design of this research was a survey. The researcher involment in this research was moderate, using non-contrived study setting. The result of this research concluded that promotion had bigger effect on forming the intention to consume snacks among children, compared to the reference groups.Key Words: Product attribute, reference groups, intention to consume, impulsice buying, influence power.